PERUBAHAN STATUS GIZI PADA ANAK BALITA GIZI KURANG YANG MENDAPATKAN PEMBERIAN MAKANAN TAMBAHAN (PMT) DI WILAYAH KERJA PUSKESMAS TUMINTING - Meildy E Pascoal; Irza N Ranti; Ridel D Tolandang (POLTEKKES KEMENKES MANADO, 2017)
Less nutrition is a health problem due to nutritional deficiencies or deficiencies necessaryfor growth, thinking, and life-related activities. Adaptive nutrient deficiency is mild to severe.Nutrition is less common in children aged less than 5 years. Supplementary feeding ininfants is an intervention program for toddlers who suffer from less protein calories thataims to meet the nutritional needs of toddlers in order to improve the nutritional status to begood. This study aims to determine whether there is a change in nutritional status inunderweight children under-five who get additional feeding (PMT). This type of researchuses quasi experimental research with one group pre-post test design. A total of 36children under five nutrition less studied as research subjects. The data collected includesinitial weight, weight gain after supplementary feeding.The result of statistic test by using Paired Samples Test The initial body weight and weightgain of 1 got significant value 0,000 (p <0,05), which can be concluded that H1 acceptedthat there is a change of nutritional status in children less nutrition less, Then for the weightBody giving 2 and body weight giving 3 got significant value 0,000 (p <0,05), which can beconcluded that H1 accepted that there is change of nutritional status in children under fivenutrition less. Conclusion there is a change in nutritional status in under-fives children lessnutrition as long as given additional food (PMT).